Impact of perceived supervisor support and leader-member exchange on employees’ intention to leave in public sector museums: A parallel mediation approach - Asif, Muhammad; Li, Mingxing; Hussain, Abid; Jameel, Arif; Hu, Weijun (Frontiers in Psychology, 2023)
High staff turnover in certain public sector organizations in Pakistan is a challenging problem, and organizations strive to reduce this issue using different mechanisms. Therefore, this research investigates the parallel mediation impact of perceived organizational support (POS) and organizational citizenship behavior (OCB) on the relationships among perceived supervisor support (PSS), leader-member exchange (LMX), and employee’s intention to leave (IL). Data were collected from 482 employees working in public sector museums in Pakistan in three waves. Structural equation modeling (SEM) with a two-step approach was used to evaluate the data. The research found that both POS and OCB mediate the negative relationship between PSS and IL and between LMX and IL in a parallel mediation mechanism. Public sector museums should focus on providing visible supervisory support and develop a healthy work environment where the exchange relationship between supervisors and subordinates strengthens to reduce the possibility of the employee's leave intentions.